Triboelectrification Based on the Waste Waterproof Textiles for Multisource Energy Harvesting - Kushal Ruthvik Kaja; Sugato Hajra; Swati Panda; Mohamed A. Belal; Phakkhananan Pakawanit; Naratip Vittayakorn; Chris Bowen; Hamideh Khanbareh; Hoe Joon Kim (My University, 2024)
Abstract The demand for sustainable energy resources to power sensor networks such as consumer electronics, agricultural technologies, digital forest management, and home automation is rapidly increasing. There are sustainability challenges to consider, where waste waterproof textiles are critical to encourage the development of a circular economy in the development of new energy technologies. This present work focuses on the utilization of direct waste waterproof textiles to design two types of triboelectric nanogenerator (TENG), which include a liquid‐solid based TENG (L‐S TENG) and a flapper‐type TENG. The bottom electrode configuration for the L‐S TENG and single electric mode working mechanism is considered for the flapper‐type TENG. Waste waterproof textiles can lead to a possible expansion of sustainable material for energy harvesters. The raincoat textile‐based L‐S TENG (L‐STENG‐R) is able to generate 0.5 V at a tilt angle of 50 degrees and power of 0.41 nW. TENGs based on discarded waterproof textiles are further utilized to demonstrate their phase change sensing, along with wind and water energy harvesting. This approach focus on decreasing waste and lower dependency on traditional resources to support environmentally responsible energy alternatives.
Keywords: Nanogenerator; Advanced Sensor and Energy Harvesting Materials